Case report: A case of brucellosis misdiagnosed as coronavirus disease 2019/influenza in China - Shuai Qin; Dongyue Lv; Ran Duan; Xiaojin Zheng; Asaiti Bukai; Xinmin Lu; Qun Duan; Mingrun Yu; Huaiqi Jing; Xin Wang (Frontiers Media S.A., 2023)
Brucellosis is an important zoonosis and a multisystem disease. The signs and symptoms of brucellosis are not specific. In the clinical, brucellosis is often ignored and misdiagnosed. We report a case of brucellosis who was misdiagnosed as coronavirus disease 2019 (COVID-19)/influenza and received delayed treatment during strict COVID-19 control. The neglect of other diseases due to COVID-19 and empirical diagnosis and treatment by medical staff are part of the reasons for misdiagnosis. Otherwise, the normal erythrocyte sedimentation rate (ESR), increased white blood cell count (WBC), and increased neutrophil count (NEUT) of this patient was also a cause of misdiagnosis, which is an important reminder for diagnosis. For patients with the unknown origin of fever and other symptoms related to brucellosis, especially those from endemic areas of brucellosis, brucellosis screening is a priority item, and grassroots doctors should be vigilant and standardize the diagnosis and treatment based on epidemiology history, clinical manifestation, and laboratory tests according to the diagnostic criteria of brucellosis.